2016
DOI: 10.1530/eje-16-0223
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous inactivating CaSR mutations causing neonatal hyperparathyroidism: function, inheritance and phenotype

Abstract: There is a significant correlation between in vitro functional impairment of the CaSR at physiologic calcium concentrations and the severity of alterations in calcium homeostasis in patients. Whether a particular genotype leads to NHPT or FHH appears to depend on additional predisposing genetic or environmental factors. An individual therapeutic approach appears to be warranted for NHPT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
2
26
0
2
Order By: Relevance
“…Some centers distinguish between NSHPT and neonatal hyperparathyroidism (NHPT) on the basis of homozygous and heterozygous CaSR mutations, respectively. NHPT may be associated with less marked and symptomatically transient hypercalcemia than NSHPT, with some patients developing symptomless FHH, and therefore not requiring parathyroid surgery . This highlights the value of CASR mutational analysis in distinguishing NSHPT from NHPT.…”
Section: Pth‐dependent Hypercalcemiamentioning
confidence: 93%
“…Some centers distinguish between NSHPT and neonatal hyperparathyroidism (NHPT) on the basis of homozygous and heterozygous CaSR mutations, respectively. NHPT may be associated with less marked and symptomatically transient hypercalcemia than NSHPT, with some patients developing symptomless FHH, and therefore not requiring parathyroid surgery . This highlights the value of CASR mutational analysis in distinguishing NSHPT from NHPT.…”
Section: Pth‐dependent Hypercalcemiamentioning
confidence: 93%
“…Mutant sensors in the plasma membrane are major contributors to hyperplasia, which is usually observed in the four glands in NSHPT [17]. The main mutations reported in this condition are compound homozygous or heterozygous inactivating mutations of CASR or sometimes simply de novo occurring heterozygotes [37, 38], such as the R185Q and R227Q mutations, which are the cause of alterations in the MAP-kinase (MAPK) pathway.…”
Section: Genetic Causesmentioning
confidence: 99%
“…It was formerly assumed that a dominant negative effect and/or paternal inheritance could have modified the clinical presentation. Recent functional studies, however, have found no evidence for either effect [38] ( Fig. 4 ).…”
Section: Dysmagnesemia Due To Ion Channel/transporter Mutations In Thmentioning
confidence: 83%